IMPROVING DIGITAL LITERACY AND ADOLESCENT MENTAL HEALTH IN THE SOCIAL MEDIA ERA - Sufyan; Maimun; Muhammad Yassir; Yonoriadi; Alfina; Nurrisma; Ismail; Riyan Maulana; Saiful Marhaban; Zainuddin; Rahmat Arfan; Muridha Hasan; Deni Trianda Pitri; Sabitah; Lusi Tutur Mulia; Zeni Abdi (CV. Naskah Aceh, 2025)
The rapid rise of social media usage among adolescents presents both opportunities and challenges, particularly concerning mental health and digital literacy. In the digital age, adolescents must navigate complex virtual environments while maintaining psychological well-being. This community service program aimed to enhance digital literacy and promote mental health awareness among school-aged adolescents in Aceh. The activity involved 25 participants aged 15–24, drawn from various schools and youth communities. Implemented over two days, the program employed a quasi-experimental design, combining interactive education, case discussions, and role-play simulations. Pre-test and post-test evaluations measured changes in participants' knowledge levels. The results indicated a significant improvement in understanding digital literacy and mental health concepts, as evidenced by a Wilcoxon test result of p = 0.010 (< 0.05). These findings underscore the effectiveness of interdisciplinary educational interventions in equipping adolescents with critical digital skills and emotional resilience in the era of pervasive social media. The program highlights the importance of collaborative efforts among educators, families, and communities in fostering safe, informed, and mentally healthy digital engagement among youth.